PENGARUH BID ASK SPREAD, MARKET VALUE, DAN DIVIDEND PAYOUT RATIO TERHADAP HOLDING PERIOD SAHAM BIASA (Studi Pada Saham Indeks Lq-45 Periode 2014 - 2016) - Dania Nabila Clarasati; Saparila Worokinasih (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
This study examined the Holding Period of the shares of LQ-45 Index in the Indonesia Stock Exchange during period 2014-2016. The sample was 14 companies which always listed in LQ-45 Index during the research period. The data used are secondary data retrieved by the method of documentation. From the test results of the coefficient of determination (R2) obtained a value of 55,6% Holding Period can be explained by Bid Ask Spread, Market Value, and Dividend Payout Ratio, while the rest 44,4% explained by other factors outside the variable Bid Ask Spread, Market Value, and Dividend Payout Ratio. From the results of the partial hypothesis testing (t test) obtained the result that variable Bid Ask Spread has not significant influence on the holding period. Variable Market Value and Dividend Payout Ratio has significant influence on Holding Period. From the results of hypothesis testing significantly (Ftest) can be said there is a significant influence silmutaneously between the Bid Ask Spread, Market Value, and Dividend Payout Ratio of the Holding Period. Keywords: Bid Ask Spread, Market Value, Dividend Payout Ratio, Holding Period, LQ-45 Index. АBSTRАK Penelitian ini menguji Holding Period saham-saham Indeks LQ-45 di Bursa Efek Indonesia selama periode 2014-2016. Sampel penelitian ini adalah 14 perusahaan yang selalu masuk dalam daftar Indeks LQ-45 selama periode penelitian. Data yang digunakan merupakan data sekunder yang diambil dengan metode dokumentasi. Dari hasil Uji Koefisien Determinasi (R2) didapat nilai sebesar 55,6% Holding Period dapat dijelaskan oleh Bid Ask Spread, Market Value dan Dividend Payout Ratio, sedangkan sisanya 44,4% dijelaskan oleh faktor lain di luar variabel Bid Ask Spread, Market Value dan Dividend Payout Ratio. Dari hasil pengujian hipotesis secara parsial (uji t) diperoleh hasil bahwa variabel Bid Ask Spread tidak berpengaruh signifikan terhadap Holding Period. Variabel Market Value dan Dividend Payout Ratio berpengaruh signifikan terhadap Holding Period. Dari hasil pengujian hipotesis secara simultan (uji F) dapat dikatakan bahwa Bid Ask Spread, Market Value dan Dividend Payout Ratio berpengaruh signifikan terhadap Holding Period. Kata Kunci: Bid Ask Spread, Market Value, Dividend Payout Ratio, Holding Period, Indeks LQ-45.